Esophagogastric junction distensibility measurements during hydraulic dilation therapy in achalasia patients. (1st February 2016) - Kappelle, Wouter F.W.; Bogte, Auke; Siersema, Peter D.
SUMMARY: Increasing evidence suggests that esophagogastric junction (EGJ) distensibility is predictive of long-term clinical success after achalasia treatment. A new commercially available hydraulic dilation balloon is capable of measuring EGJ opening diameters whilst simultaneously dilating the EGJ. Deployed alongside the endoscope under direct visualization, it is used for dilation of the lower esophageal sphincter in patients with achalasia. Impedance measurement electrodes are incorporated in the catheter shaft in the dilation balloon, which allows measuring the diameter of the EGJ and displaying it in real time before, during and after dilation. This obviates the need for fluoroscopy during the dilation procedure. The extent of recoil of the EGJ after dilation potentially provides a measurement that could be incorporated into a clinical rule for predicting therapeutic success after dilation.